KOMUNIKASI PEMUDA INDONESIA DALAM TANTANGAN MEDIA MAINSTREAM DAN NILAI-NILAI MODERASI BERAGAMA - Luqman Al Hakim; Muhammad Faiz (Program Studi Komunikasi dan Penyiaran Islam Pascasarjana UIN KHAS Jember, 2021)
Abstract This article discusses the roles and challenges of Indonesian youth in front of political currents and global dynamics. Youth as an important asset of the nation in its future sustainability, including for Indonesia which has a dominant youth population, is an important capital for nation building. The world of mass media (printed and online) which is developing massively, is free to be filled by any group (party) whether with positive interests or even those with bad intentions. Therefore, the role of youth becomes central in rejecting negative media propaganda and within the framework of spreading the values ​​of moderation. The existence of youth can be present by coloring the media and filling it with various positive agendas. This article concludes that Indonesian youth in the process of building and advancing the nation are valuable assets that must be empowered as part of a solution that puts forward the values ​​of national moderation and other values ​​of the Indonesian nation has. Key Words: Youth, Media, Nation and Moderation.